2022
DOI: 10.1186/s12978-022-01363-4
|View full text |Cite
|
Sign up to set email alerts
|

Fertility treatments and the risk of preterm birth among women with subfertility: a linked-data retrospective cohort study

Abstract: Background In vitro fertilization (IVF) births contribute to a considerable proportion of preterm birth (PTB) each year. However, there is no formal surveillance of adverse perinatal outcomes for less invasive fertility treatments. The study objective was to describe associations between fertility treatment (in vitro fertilization, intrauterine insemination, usually with ovulation drugs (IUI), or ovulation drugs alone) and preterm birth, compared to no treatment in subfertile women. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
(53 reference statements)
0
10
1
Order By: Relevance
“…The prevalence of preterm birth in our study was much higher than the global prevalence, with a quarter (25.9%) of the newborns being preterm. Advanced maternal age is recorded in the literature as a risk factor for very premature birth, but in our study, there was no correlation between the age of mothers and prematurity [ 37 40 ]…”
Section: Discussioncontrasting
confidence: 62%
“…The prevalence of preterm birth in our study was much higher than the global prevalence, with a quarter (25.9%) of the newborns being preterm. Advanced maternal age is recorded in the literature as a risk factor for very premature birth, but in our study, there was no correlation between the age of mothers and prematurity [ 37 40 ]…”
Section: Discussioncontrasting
confidence: 62%
“…(1-2) However, the topic of concern regarding the prevalence of congenital anomalies in pregnancies resulting from IVF and ICSI has been a topic of ongoing debate within the medical community (1)(2)(3)(4)(5). Potential hypotheses behind this phenomenon include factors such as maternal age at the time of IVF/ICSI, multiparity, and innate susceptibility to natural congenital pathologies (29)(30). Some causes of female infertility can predispose embryos to malformations and increase the risk of prematurity (30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Potential hypotheses behind this phenomenon include factors such as maternal age at the time of IVF/ICSI, multiparity, and innate susceptibility to natural congenital pathologies (29)(30). Some causes of female infertility can predispose embryos to malformations and increase the risk of prematurity (30)(31). Moreover, the risk of prematurity is heightened by multiparity, which is more prevalent in IVF/ICSI cases (28-31).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that preterm birth is associated with many factors, such as maternal demographic characteristics, nutritional status, pregnancy history, adverse behaviors, and so on [ 6 ]. It was known that preterm birth was predominantly related to multiple gestation births, regardless of IVF cycles or intrauterine insemination (IUI) cycles [ 7 ]. Some researchers thought that the patient's own infertility factors might contribute to the preterm birth rather than the IVF procedures themselves [ 8 ].…”
Section: Introductionmentioning
confidence: 99%